Heightened exercise-induced oxidative stress at simulated moderate level altitude vs. sea level in trained cyclists - Wadley, A. J.; Svendsen, I. S.; Gleeson, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Altitude exposure can exaggerate the transient increase in markers of oxidative stress observed following acute exercise. However, these responses have not been monitored in endurance-trained cyclists at altitudes typically experienced while training. Endurance trained males (n = 12; mean (± SD) age: 28 ± 4 years, VO2max 63.7 ± 5.3 ml/kg/min) undertook two 75-min exercise trials at 70% relative VO2max; once in normoxia and once in hypobaric hypoxia, equivalent to 2000m above sea level (hypoxia). Blood samples were collected before, immediately after and 2 h postexercise to assess plasma parameters of oxidative stress (protein carbonylation (PC), thiobarbituric acid reactive substances (TBARS), total antioxidant capacity (TAC) and catalase activity (CAT)). Participants cycled at 10.5% lower power output in hypoxia vs. normoxia, with no differences in heart rate, blood lactate or rating of perceived exertion observed. PC increased and decreased immediately after exercise in hypoxia and normoxia respectively (nmol/mg/protein: Normoxia—0.3 ± 0.1, Hypoxia + 0.4 ± 0.1; both p < .05). CAT increased immediately postexercise in both trials, with the magnitude of change greater in hypoxia (nmol/min/ml: Normoxia + 12.0 ± 5.0, Hypoxia + 27.7 ± 4.8; both p < .05). CAT was elevated above baseline values at 2 h postexercise in Hypoxia only (Normoxia + 0.2 ± 2.4, Hypoxia + 18.4 ± 5.2; p < .05). No differences were observed in the changes in TBARS and TAC between hypoxia and normoxia. Trained male cyclists demonstrated a differential pattern/ timecourse of changes in markers of oxidative stress following submaximal exercise under hypoxic vs. normoxic conditions.